The Impact of Two Types of Mycoplasma gallisepticum Vaccines on Broiler Chicken Respiratory System. - Saad Muofaq Al-Tamimi; Abtisam Jawad Ali; Rawah A. Faraj (University of Thi-Qar Journal of agricultural research, 2023)
This study aimed to evaluate the effect of vaccinating 1-day-old broilerchicks with two commercial vaccines such as live chronic respiratorydisease F strain (CRDF) and killed Mycoplasma gallisepticum (MG)vaccines on the respiratory system. For this purpose, one-day-old broilerchicks (n=120) were randomly divided into four groups; (n=30 birdseach). All groups were treated as followed: G1(CRDF): chicks werevaccinated with live CRDF vaccine (eye drop one drop 0.03ml/dose/10 5 ),G2 (killed MG): chicks were vaccinated with killed MG vaccine injectionwith 0.3ml s.c /3 x10 10 C.F.U/ml), G3: chicks were combined vaccinatedwith killed MG and CRDF live vaccines G4: served as controlunvaccinated group. The vaccination was performed at one day old in G1(CRDF), G2(killed MG), and G3 (killed MG and live CRDF). Thehistopathological changes of the trachea and air sacs were examined andevaluated at 35 days old. The results of histopathological examination ofair sacs in the G1(CRDF) revealed various mild epithelial hyperplasiawith papillary-like growth, subepithelial lymphocytic infiltration, in G2(killed MG), showed hyperplastic epithelial surfaces with moderatelymphocytic infiltration mainly around congestion capillaries. While G3(killed MG and CRDF) showed focal epithelial hyperplasia (villus-like),and perivascular lymphocytic aggregation in laminar C.T. Whereas G4(control) showed normal structures without any histopathological lesions.In the trachea the histopathological changes in G1(CRDF) showed focallymphocytic aggregation with a follicle-like appearance, another sectionshowed focal epithelial and cilia loss with goblet cell hypertrophy of theadjacent gland. G2 (killed MG) showed partial loss of thin mucosa withmild and desquamation lymphocytic infiltration in lamina propria,G3(killed MG and CRDF) showed diffuse mononuclear cells (MNCs)infiltration in tracheal mucous and submucosa with evidence of cysticdilution of adjacent gland together G4 control tracheal tissue showednormal structure without any lesions. Finally, it was determined thatvaccination with killed MG and live CRDF vaccines caused a moreobvious immune reaction (lymphoproliferative infiltration) in therespiratory system, including the trachea and air sac than the vaccinationwith combined killed and live vaccines, while the live Mycoplasmavaccines individually caused minor damage, particularly in the trachea.